2007
DOI: 10.1194/jlr.m600340-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for in situ ethanolamine phospholipid adducts with hydroxy-alkenals

Abstract: Hydroxy-alkenals, such as 4-hydroxy-2(E )-nonenal (4-HNE; from n-6 fatty acids), are degradation products of fatty acid hydroperoxides, including those generated by free radical attack of membrane polyunsaturated fatty acyl moieties. The cytotoxic effects of hydroxy-alkenals are well known and are mainly attributable to their interaction with different molecules to form covalent adducts. Indeed, ethanolamine phospholipids (PEs) can be covalently modified in a cellular system by hydroxy-alkenals, such as 4-HNE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…Furthermore, inhibition of ER stress blocks acrolein-induced increases in mRNA levels of the proinflammatory cytokines TNF␣, IL-6, and IL-8 (33). As ␥KA, HNE, and acrolein all modify PE (8,11,13,(15)(16)(17)(18), our finding that ␥KA-PE induces CHOP, IL-8, and MCP-1 expression raises the possibility that these other aldehydes also mediate their inflammatory effects by forming modified PE, which induce ER stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inhibition of ER stress blocks acrolein-induced increases in mRNA levels of the proinflammatory cytokines TNF␣, IL-6, and IL-8 (33). As ␥KA, HNE, and acrolein all modify PE (8,11,13,(15)(16)(17)(18), our finding that ␥KA-PE induces CHOP, IL-8, and MCP-1 expression raises the possibility that these other aldehydes also mediate their inflammatory effects by forming modified PE, which induce ER stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Since lipid aldehydes are rather long-lived, they can reach and attack targets such as phospholipids, DNA, and proteins distant from their original site of formation (3,17,40,52).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being markers of lipid peroxidation in vivo, 4-HNE and 4-HHE induce noxious effects on biological systems. These lipid aldehydes are prone to react with thiol and amine moieties and produce Schiff base and/or Michael adducts with biomole cules, such as proteins, DNA, and phospholipids ( 12,13 ). Numerous studies reported the genotoxicity and cytotoxicity of these 4-hydroxy-2-alkenals on tissues and cells in pathophysiological contexts (14)(15)(16), but nothing is known to date about the possible contribution of 4-hydroxy-2-alkenals present in food products, their fate after ingestion, and their metabolic effects.…”
Section: Caco-2/tc7 Cell Culture and Treatmentmentioning
confidence: 99%